Fairness that money can buy: Procedural egalitarianism in practice - Werner Güth; Hartmut Kliemt (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
We suggest that procedures of monetarized bidding can facilitate co-operation in Elinor Ostrom type common(s) projects without crowding out communitarian faculties of self-governance. Axioms securing procedurally egalitarian bidding on the basis of declared monetary evaluations are introduced. They guarantee that all realized changes of a status quo are in an objective (pecuniary) sense equally advantageous for all members of the community. Some empirical evidence that procedurally fair bidding can promote communitarian co-operation rather than crowding it out, is presented. The practical scope and limits of procedural egalitarianism need further empirical exploration, though.
Keywords: H4; H61; D62; D63; D71; 330; fair procedures; egalitarian mechanisms; unanimity; constitutional political economy; non-state communities; governing the commons; crowding out